Συμβολή στη Μικρασιάτικη αγιολογία: Οι νεομάρτυρες της Σμύρνης - Γριμάνης, Σταύρος Δ. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2011)
In this essay the author gives a list of all known martyrs, who were executed by non Christian authorities during the long period between the 13th and 19th c. in Smyrna of Asia Minor. A bibliographical note for each one of these martyrs accompanies the brief biographical note supplied. Before listing the martyrs, the author attempts to explain basic concepts (like neomartyrs) and to present the books and compilations which were used as sources. After the list follows a theoretical chapter in which the author specifies the main aspects of the research based upon these texts. The ideology/religion, the societies and the key personalities of this period form an interesting combination. Only by taking into account these aspects could the researcher shed light on these texts. Conversely, these same texts can help the reader in gaining a better understanding of the subject.